Praktik Diskursif Amerika Serikat dalam Membangun Narasi Terorisme Global : Studi Kasus Kejahatan oleh Ali Muhammad Brown dan Stephen Craig Paddock - Sapen Sartika Unyi Putri; Mohamad Rosyidin; Muhammad Faizal Alfian (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The United States of America as a super power, is able to create and build knowledge, 'reality', and global narratives that are trusted by the world community according to their interests. This is no exception in terms of terrorism. The purpose of this study is to explain how the discursive practices carried out by the US Government and media in building a global narrative related to terrorism through case studies of crimes committed by Ali Muhammad Brown and Stephen Craig Paddock. The method used in this research is a qualitative descriptive approach. This research is viewed from the perspective of poststructuralism which has not been found in previous studies. The result of this study is that the identification of who deserves the label of terrorist in the United States occurs only in Muslims and especially those who have people of color. This occurs as a result of the social construction that develops in global society through the discursive practices of the United States Government and Media. From the results of this study, it shows how discursive practice can be used in shaping existing reality and knowledge, so the discourse will contain different meanings depending on who interprets it. In addition from this research, it can be concluded that the reality and narrative as well as knowledge related to global terrorism are not free values but are biased towards political interests and are built by constructions and discursive practices developed by the ruling state.